1984
DOI: 10.1111/j.1768-322x.1984.tb00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the gonad cytoplasmic core during oogenesis of the nematode Caenorhabditis elegans

Abstract: In order to elucidate the function of the cytoplasmic core (or rachis: a structure specific of the nematode gonads), we have carried out a cytological study of this structure in the free-living nematode Caenorhabditis elegans, in wild-type and in several mutant strains showing an abnormal gametogenesis. We also performed an ultrastructural radioautographic study of RNA synthesis during oogenesis in order to examine the part played by the rachis in the transport of nutritive substances. Our results evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 0 publications
0
40
0
1
Order By: Relevance
“…If germline CGH-1/CAR-1 foci are involved in storage or translational regulation but not degradation of maternal mRNA, it could explain why they increase in intensity and appear in the gonad core in parallel with newly synthesized mRNA (Fig. 3A,J) (Gibert et al, 1984;Navarro and Blackwell, 2005;Navarro et al, 2001;Schisa et al, 2001), and why physical association between CGH-1 orthologs and the mRNA decapping/degradation machinery has not been detected in the metazoan germline (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…If germline CGH-1/CAR-1 foci are involved in storage or translational regulation but not degradation of maternal mRNA, it could explain why they increase in intensity and appear in the gonad core in parallel with newly synthesized mRNA (Fig. 3A,J) (Gibert et al, 1984;Navarro and Blackwell, 2005;Navarro et al, 2001;Schisa et al, 2001), and why physical association between CGH-1 orthologs and the mRNA decapping/degradation machinery has not been detected in the metazoan germline (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…These results provide a mechanistic explanation for previous observations on the distribution of RNA in the gonad. Labeled-uridine incorporation showed that nascent RNA (largely rRNA) first appears in pachytene nuclei, and subsequently accumulates in the gonad core before appearing in oocyte cytoplasm (Gibert et al, 1984;Schisa et al, 2001;Starck, 1977). Because materials are transported from numerous pachytene-stage nuclei into single, enlarging oocytes, the pachytene-stage nuclei can be considered a nurse cell population.…”
Section: Discussionmentioning
confidence: 99%
“…elegans gonads do not contain morphologically distinct nurse cells, and none of the germline nuclei appear to be highly polyploid when stained for DNA (Hirsh et al, 1976) (our unpublished data). Prior to oogenesis, most germ cells appear to be highly active transcriptionally, producing RNA that accumulates in the gonad core (Gibert et al, 1984;Starck, 1977). As the transcriptionally quiescent oocytes enlarge, they presumably incorporate core cytoplasm that they, or other germ cells, synthesized during earlier developmental stages and deposited in the core.…”
Section: Introductionmentioning
confidence: 99%
“…Two uORFs are boxed, and the ATG of the GNA-2 ORF is in bold and underlined. mosomes become highly condensed in late-stage oocytes (diakinesis), almost no de novo RNA synthesis occurs (Gibert et al 1984;Schisa et al 2001) and RNA polymerase II becomes inactive (Kelly et al 2002). Therefore, most maternal transcripts, including GLD-1 targets rme-2, oma-1, and oma-2 mRNAs, are transcribed mainly in pachytene-stage germ cells in the distal region and transported into the common cytoplasmic core.…”
Section: Gna-2 Mrna Is a Naturally Occurring Target Of Nmd And Gld-1 mentioning
confidence: 99%